2011
DOI: 10.1111/j.1399-3054.2011.01517.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of fructan dynamics in two wheat cultivars with different capacities of accumulation and remobilization under drought stress

Abstract: Remobilization of stored carbohydrates in the stem of wheat plants is an important contributor to grain filling under drought stress (DS) conditions. A massive screening on Iranian wheat cultivars was performed based on stem dry weight changes under well-watered and DS conditions. Two cultivars, Shole and Crossed Falat Hamun (CFH), with different fructan accumulation and remobilization behavior were selected for further studies. Water-soluble carbohydrates (WSCs) and fructan metabolizing enzymes were studied b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
55
0
18

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(77 citation statements)
references
References 61 publications
4
55
0
18
Order By: Relevance
“…Genotype DHTW-60, WH-1105 & HD-2967 showed higher SRM at different time of drought application and different sowing condition in peduncle and penultimate internode (Table 1an 2). The results of present investigation are supported by earlier finding of Gupta et al, 2011;Joudi et al, 2012;Zhang et al, 2014). Sharifi et al, (2017) found similar result in wheat genotypes under water-deficit treatments with 50 to 80 % higher mobilization than the in well-watered treatments, which indicates that water deficits promoted remobilization.…”
Section: Mean Sum Of Squaresupporting
confidence: 91%
“…Genotype DHTW-60, WH-1105 & HD-2967 showed higher SRM at different time of drought application and different sowing condition in peduncle and penultimate internode (Table 1an 2). The results of present investigation are supported by earlier finding of Gupta et al, 2011;Joudi et al, 2012;Zhang et al, 2014). Sharifi et al, (2017) found similar result in wheat genotypes under water-deficit treatments with 50 to 80 % higher mobilization than the in well-watered treatments, which indicates that water deficits promoted remobilization.…”
Section: Mean Sum Of Squaresupporting
confidence: 91%
“…The grain filling of cereals depends on carbon from two sources: current assimilation and remobilization of reserves stored in the stem either pre-or post-anthesis Joudi et al 2012). Most estimates of the contribution of stem reserves to grain filling are 20-50 % of the final grain weight in non-stress conditions (Rawson and Evans 1971;Schnyder 1993;Wardlaw and Willenbrink 2000).…”
Section: Introductionmentioning
confidence: 99%
“…As the total amount of stem contributions to grain yield was the same in the taller and shorter cultivars (Joudi unpublished), the decrease in carbohydrate accumulation and remobilization imposed by length reduction is expected to be compensated by higher SSW in the shorter cultivars. Joudi et al (2012) reported that both carbohydrate amounts and remobilization efficiency per unit stem length were higher in modern cultivars, as compared to the old ones. Therefore, the reduction of stem length (data not shown) and an increase of SSW in modern cultivars suggest that plant breeders should pay more attention to SSW than to stem weight or length.…”
Section: Discussionmentioning
confidence: 99%